Fixed-dose combinations in the treatment of hypertension to increase adherence - T. E. Morozova; E. O. Samokhina (Российский кардиологический журнал)
Despite a wide range of antihypertensive drugs, blood pressure (BP) control often remains unsatisfactory, and every year the number of people with uncontrolled high BP increases. One of the strategies aimed at improving medical adherence is the use of fixed-dose combinations of 2 antihypertensive drugs for starting therapy, and, if necessary, 3 drugs. Initiation of therapy with 2 drugs in one tablet is recommended for most patients. A review of algorithms for choosing combinations of antihypertensive drugs in different clinical situations, including in patients with various comorbid conditions, is presented. Simplification of treatment regimens makes it possible to choose the most optimal solutions in various clinical situations, in particular, with stage I-II hypertension, with a combination of hypertension with chronic kidney disease, as well as with a combination of hypertension with coronary artery disease and a number of other diseases.